Botulinum toxin type A suppresses arterial vasoconstriction by regulating calcium sensitization and the endothelium-dependent endothelial nitric oxide synthase/soluble guanylyl cyclase/cyclic guanosine monophosphate pathway: An in vitro study. Issue 16 (November 2019) - Hu, Liang; Feng, Ya; Liu, Wuchao; Jin, Lingjing; Nie, Zhiyu
Botulinum toxin type A (BTX-A) is a potent neurotoxin that causes relaxation of striated muscle by inhibiting the release of acetylcholine at the neuromuscular junction. Some studies have suggested that BTX-A treatment for Raynaud syndrome is safe and effective with few adverse reactions. However, the underlying mechanism remains unclear. In the present study, we used both arterial rings isolated from rabbits and human microvascular endothelial cells (HMEC-1) to evaluate the mechanism underlying the effects of BTX-A on arterial vasoconstriction induced by 5-hydroxytryptamine. The roles of calcium sensitization and the endothelial nitric oxide synthase (eNOS)/soluble guanylyl cyclase (sGC)/cyclic guanosine monophosphate (cGMP) pathway were investigated. BTX-A caused a concentration-dependent decrease in the contraction of endothelium-intact arteries and significantly reduced calcium sensitization in the arteries. Inhibitors of eNOS (L-NAME) and sGC (methylene blue) both significantly abolished the vasodilatory action of BTX-A. Furthermore, BTX-A increased eNOS activity and the cGMP level in dose- and time-dependent manners and increased eNOS and sGC protein levels in a time-dependent manner in HMEC-1. Taken together, these findings indicate that BTX-A suppresses arterial vasoconstriction by regulating smooth muscle calcium sensitization and the eNOS/sGC/cGMP pathway. Impact statement: Raynaud syndrome (RS), usually caused by cold or mental stress, may lead to cyanosis and reactive hyperemia accompanied by pain or paresthesia. Although a variety of drugs have been used to alleviate the symptoms, the effects have not been satisfactory, so there is an urgent need to explore new alternative treatments. The present study investigated the mechanism underlying the effects of botulinum toxin type A (BTX-A) on arterial vasoconstriction, which may provide new approaches for RS. We found that BTX-A suppresses arterial vasoconstriction by regulating smooth muscle calcium sensitization and the endothelial nitric oxide synthase (eNOS)/soluble guanylyl cyclase (sGC)/cyclic guanosine monophosphate (cGMP) pathway. These findings clarify the underlying mechanism of the effects of BTX-A on arterial vasoconstriction and provide new theoretical support for the use of BTX-A on RS. It may also help us to develop new medicines which regulate calcium sensitization and the eNOS/sGC/cGMP pathway against RS.